MEMÓRIA, IDENTIDADE E CULTURA NO VOCABULÁRIO DO ESCRITOR JOÃO BRASIL | MEMORY, IDENTITY AND CULTURE IN THE VOCABULARY OF WRITER JOÃO BRASIL - Soares, Eliane Pereira Machado (Estudos Linguísticos e Literários, 2019)
Resumo: Este trabalho resulta de uma pesquisa sobre o vocabulário da obra literária do autor memorialista João Brasil Monteiro, da cidade de Marabá, Estado do Pará, com o objetivo de estabelecer relações entre língua e identidade e a memória coletiva local. O referencial teórico e metodológico remete à análise léxico-semântica de lexias, organizadas em campos lexicais Coseriu (1979). A organização do vocabulário em si apresentará os verbetes em ordem alfabética, em campos semânticos, com as respectivas informações gramaticais, definições e remissivas, para tanto utilizaremos a ferramenta computacional Lexique Pro. Até o momento já foram identificados cerca de 600 itens lexicais. Abstract: This work results from a research on the vocabulary of the literary work of the memorialist author João Brasil Monteiro, from the city of Marabá, State of Pará, in order to establish relations between language and identity and local collective memory. The theoretical and methodological referential refers to the lexical-semantic analysis of lexias, organized in lexical fields Coseriu (1979). The organization of the vocabulary itself will present the entries in alphabetical order, in semantic fields, with the respective grammatical information, definitions and references, for which we will use the Lexique Pro computational tool. To date, about 600 lexical items have been identified. Keywords: Lexicon; Regional Language; Vocabulary.